A revolution of the mind Radical Enlightenment and the intellectual origins of modern democracy - Israel, Jonathan I. (Princeton Princeton University Press, 2010)
Democracy, free thought and expression, religious tolerance, individual liberty, political self-determination of peoples, sexual and racial equality--these values have firmly entered the mainstream in the decades since they were enshrined in the 1948 U.N. Declaration of Human Rights. But if these ideals no longer seem radical today, their origin was very radical indeed--far more so than most historians have been willing to recognize. In A Revolution of the Mind, Jonathan Israel, one of the world's leading historians of the Enlightenment, traces the philosophical roots of these ideas to what were the least respectable strata of Enlightenment thought--what he calls the Radical Enlightenment.
Includes bibliographical references and index.
Keywords: Political science--Europe--History--18th century